(untitled) (CIPEEX, 2025)
The article discusses the consequences of the intensive use of pesticides in Goiás agriculture, highlighting the impacts on public health and the environment. The study has an exploratory character and uses secondary data from sources such as DataSUS and the Mauro Borges Institute to analyze notifications of exogenous intoxications by pesticides. The analysis covers the period from 2010 to 2023 and focuses on the health macro-regions of northeastern Goiás. The results indicate a significant increase in the production of soybeans, sugarcane, and corn and in cases of intoxication and underreporting, highlighting the need for improvements in monitoring systems and stricter public policies to protect human health and the environment.